The Implementation of Waqf to Actualize Economic Justice Based on Islamic Law - Helza Nova Lita (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2020)
Economic justice is one of the objectives of the implementation of Islamic economic system. Waqf is one of the instruments of Islamic economics. It is interesting to study the implementation of economic justice through waqf and how its regulation in Indonesia. This article employed normative juridical method. Based on the Article 22 of the Law Number 41 of 2004 on Waqf, the purpose of waqf is not solely for the purpose of ritual. It can also be used to realize economic prosperity. Based on these provisions, waqf can be managed for the economic empowerment of the people. This is related to the efforts of the improvement of the economic welfare of the people, especially for the weak economic class. According to Islamic teachings, distributive justice is economic justice based on the Holy Quran, Chapter al-Hasyr (59): 7. Waqf has the potential to create the economic balance of society. Because the principle of ownership, according to Islam, regulates that individuals or certain community members are not the only party who control the management of assets. The weak economic class also have the right. It is to avoid economic inequality. Thus, waqf is a solution to actualize economic justice in order to realize public welfare, which is one of Indonesia’s national goals as stated in the Preamble of the 1945 Constitution of the Republic of Indonesia.Implementasi Wakaf dalam Mewujudkan Keadilan Ekonomi Menurut Hukum IslamAbstrakKeadilan ekonomi merupakan salah satu tujuan implementasi sistem ekonomi Islam yang tercermin dari mekanisme yang ditetapkan dalam hukum Islam. Wakaf merupakan salah satu instrumen ekonomi Islam. Hal ini menarik untuk dikaji lebih lanjut, bagaimana makna keadilan ekonomi dalam Islam itu sendiri yang diimplementasikan melalui wakaf, serta bagaimana pengaturannya di Indonesia. Metode yang digunakan dalam pembahasan artikel ini adalah yuridis normatif. Berdasarkan ketentuan Pasal 22 Undang-Undang Nomor 41 Tahun 2004 tentang Wakaf, tujuan wakaf tidak semata-mata untuk kepentingan ibadah ritual semata. Namun juga dapat digunakan untuk mewujudkan kesejahteraan bidang ekonomi. Berdasarkan ketentuan tersebut, Wakaf dapat dikelola untuk pemberdayaan ekonomi umat. Hal ini sangat terkait dalam upaya  meningkatkan kesejahteraan ekonomi  masyarakat, khususnya untuk kelompok ekonomi masyarakat lemah. Keadilan disributif merupakan keadilan ekonomi menurut ajaran Islam berdasarkan Al-Qurán surat al-Hasyr [59]:7. Melalui wakaf dapat diwujudkan keseimbangan ekonomi masyarakat. Hal ini dikarenakan prinsip kepemilikan menurut Islam, mengatur bahwa pengelolaan harta tidak  hanya dikuasai secara pribadi atau kelompok anggota masyarakat tertentu saja, namun juga oleh kelompok ekonomi lemah agar tidak  terjadi ketimpangan ekonomi yang terlalu tinggi dalam masyarakat. Dengan demikian wakaf merupakan salah satu solusi untuk mewujudkan keadilan ekonomi guna mewujudkan kesejahteraan umum yang merupakan salah satu tujuan nasional Indonesia sebagaimana disebutkan dalam pembukaan UUD NRI 1945.Kata kunci: Hukum Islam, Implementasi, WakafDOI: https://doi.org/10.22304/pjih.v7n1.a1